Pests and Diseases in Foxtail Millet (Setaria italica L. Beauv.) Cultivated in The Greenhouse - Khairani, Hagia Sophia; Nurulalia, Lia; Ardie, Sintho Wahyuning (Journal of Tropical Crop Science, 2021)
Greenhouse ecosystem with more stable abiotic factors could affect the population and diversity of pests and diseases found on foxtail millet (Setaria italica L. Beauv.) compared to their natural ecosystems. We observed and identified pests and diseases in seven genotypes of foxtail millet namely “Toraja”, “ICERI 5”, “ICERI 6”, “Botok 4”, “Botok 10”, “Mauliru”, and “Hambapraing”; these activities are important for the formulation of appropriate integrated pest management techniques. Using plant samples that were at the end of their vegetative phase, we found white mycelia of Fusarium incarnatum (yellowish-white colonies) and F. verticilloides (violetish-pink colonies) covering the ear-tip of the seeds and developed rapidly leading to seed rotten symptoms in “Toraja”, “ICERI 5”, and “ICERI 6”. The disease severity remained constant after these integrated management techniques were put in place. However, abnormalities in leaves leading to failure of panicle emergence occurred in “Botok 4”, “Botok 10”, “Mauliru”, and “Hambapraing”. These were caused by the fungi Penicillium sp. Identical controlling techniques were applied to this incidence and the disease incidence was reduced. Corn leaf aphids (Rhophalosiphum maidis) and rice mealybugs (Brevenia rehi) were recorded as main insect pests with severe attack. The aphid, R. maidis, colonized the stems and were associated with the sooty mold (Capnodium sp.), resulting in wilting. The mealybugs, B. rehi, colonized the flag leaves resulting in leaf rotting. Insecticide and isolating the attacked plants were used as the controlling techniques. Red-mites (Tetranychus urticae) were also detected as indicated by chlorotic spots on the upper part of the leaves. Acaricide was used to reduce its population. The pests and diseases found in the seven genotypes of foxtail millet are commonly known to occur in Poaceae. In general, greenhouse ecosystem for foxtail millet facilitated planting with high population with lower diversity of pests and diseases compared to the open field planting.